Data Compression Technology for Optimizing Digital Learning Material Management in Repository Application using Personal Extreme Programming (PXP) - Putra, Wahyu Permana; Saputra, Hadi Kurnia; Hadi, Ahmaddul; Mursyida, Lativa (Sagamedia Teknologi Nusantara, 2024)
This research aims to create an educational environment integrated with technology through the implementation of educational technology, particularly by managing and storing digital learning device documents known as repositories. The developed Repository System aims to optimize storage management for learning device documents within an educational institution. A case study was conducted at a Vocational High School (SMK). The management and storage system for learning device documents was developed using the Personal Extreme Programming (PXP) method, adopting an adaptive and flexible agile approach. The repository system also applies data compression technology to optimize the storage capacity of learning device documents. Based on the results of the data compression testing, the developed system proved to be suitable, achieving an average storage efficiency of 40.04% for each uploaded file. This research contributes practical insights into the implementation of a repository system in an educational environment, particularly in Vocational High Schools, with a focus on curriculum transitions and the efficiency of managing learning device documents.